General Principles of Creating Electronic Dictionaries - Mokhiyakhon, Uzokova (Research Parks Publishing LLC, 2021)
The issue of electronic dictionaries has been relevant since the advent of computers and the Internet. Although electronic dictionaries have different forms: web, mobile, desktop, the creation of electronic dictionaries on any topic is based on general principles. The article focuses on these general principles and their role in Uzbek computer lexicography.